Effects of a first-year undergraduate engineering design course: survey study of implications for student self-efficacy and professional skills, with focus on gender/sex and race/ethnicity - Jessica Sperling; Menna Mburi; Megan Gray; Lorrie Schmid; Ann Saterbak (SpringerOpen, 2024)
Abstract Background Students' academic self-efficacy maximizes likelihood for success and retention, yet prior research suggests that historically underrepresented (minoritized) undergraduate students in higher education and in college-level engineering show lower self-efficacy, which has been linked to histories of systemic exclusion. To address such gaps in student success, this work examines the effect of a new first-year undergraduate engineering design course on students' self-efficacy, as measured by students' assessment of their ability to achieve engineering design goals, and their confidence in their professional skills such as teamwork, communication, and leadership. It draws upon two aligned survey studies that examine this development (a) among the students participating in the course during the academic semester and (b) among both course participants and non-participants in the year following the course. Survey results for all students were considered, with attention to specific demographic subgroups traditionally underrepresented in engineering. Results Analyses indicate effect of the course on self-efficacy and other examined constructs, such as communication and teamwork, during the course semester and continued effects in engineering design self-efficacy and tinkering self-efficacy in the year following course participation. Results also reveal differences for specific racial/ethnic and gender/sex subgroups in numerous constructs, including suggestion of specific effect for female students. Conclusions This study's focus on the implication of engineering design education on self-efficacy and other critical professional outcomes, as well as its attention to specific demographic subgroups, adds to research on engineering education and the effect of design-focused coursework using project-based learning. The study indicates an increased potential role for such coursework, as early as the first year of a university trajectory, in fostering student growth and increased representation in the field. Findings on differences by gender/sex and by racial/ethnic groups, including clearer positive effect for female students but more complexity in effect for underrepresented racial/ethnic groups, support added research probing experience and outcomes within and across these groups.